Insurance Expansion and the Utilization of Inpatient Surgery: Evidence for a "Woodwork" Effect?. (December 2015) - Ellimoottil, Chandy; Miller, Sarah; Davis, Matthew; Miller, David C.
Introduction . The impact of insurance expansion on the currently insured population is largely unknown. We examine rates of elective surgery in previously insured individuals before and after Massachusetts health care reform. Methods . Using the State Inpatient Databases for Massachusetts and 2 control states (New York and New Jersey) that did not expand coverage, we identified patients aged 69 and older who underwent surgery from January 1, 2003, through December 31, 2010. We studied 5 elective operations (knee and hip replacement, transurethral resection of prostate, inguinal hernia repair, back surgery). We examined statewide utilization rates before and after implementation of health care reform, using a difference-in-differences technique to adjust for secular trends. We also performed subgroup analyses according to race and income strata. Results . We observed no increase in the overall rate of selected discretionary inpatient surgeries in Massachusetts versus control states for the entire population (−1.4%, P = .41), as well as among the white (−1.6%, P = .43) and low-income (−2.2%, P = .26) subgroups. We did, however, find evidence for a woodwork effect in the subgroup of nonwhite elderly patients, among whom the rate of these procedures increased by 20.5% ( P = .001). Among nonwhites, the overall result reflected increased utilization of all 5 individual procedures, with statistically significant changes for knee replacement (18%, P < .01), back surgery (18%, P = .05), transurethral resection of the prostate (28%, P = .05), and hernia repair (71%, P = .03). Conclusion . Our findings suggest that national insurance expansion may increase the use of elective surgery among subgroups of previously insured patients.